Iron-biofortified pearl millet consumption increases physical activity in Indian adolescent school children after a 6-month randomized feeding trial - Pompano, Laura M.; Luna, Sarah; Ghugre, Padmini; Przybyszewski, Eric M.; Haas, Jere D. (Cambridge University Press, 2022)
Background: Iron deficiency has negative effects on voluntary physical activity (PA); however, the impact of consuming iron-biofortified staple foods on voluntary PA remains unclear. This study compared the effects of consuming iron-biofortified pearl millet or a conventional pearl millet on measures of voluntary PA in Indian school children (ages 12-16 years) during a six-month randomized, controlled feeding trial. PA data were collected from 130 children using Actigraph GT3X accelerometers for six days at baseline and endline. Minutes spent in light and in moderate-to-vigorous PA were calculated from accelerometer counts using Crouter’s refined two-regression model for children. Mixed regression models adjusting for covariates were used to assess relationships between intervention treatment or change in iron status and physical activity. Results: Children who consumed iron-biofortified pearl millet performed 22.3 (95% CI: 1.8, 42.8, p = 0.034) more minutes of light PA each day compared to conventional pearl millet. There was no effect of treatment on moderate-to-vigorous PA. The amount of iron consumed from pearl millet was related to minutes spent in light PA (estimate and 95% CI: 3.4 min/mg iron (0.3 to 6.5, p = 0.031)) and inversely related to daily sedentary minutes (estimate and 95% CI: −5.4 min/mg iron (−9.9 to −0.9, p = 0.020)). Conclusion: Consuming iron-biofortified pearl millet increased light PA and decreased sedentary time in Indian school children in a dose-dependent manner.